Towards a fair procedure for risk management - Hermansson, Hélène (Journal of risk research, 2010)
The need for fairness in risk management is frequently expressed in the risk literature. In this article, fairness is connected to the procedure for decision-making. Two models for procedural justice in the management of risks are discussed, one that focuses on a hypothetical thought experiment, and one that focuses on actual dialogue. The hypothetical approach takes John Rawls' theory of justice as a starting point. The actual inclusion approach employs Iris Marion Young's theory of inclusive deliberative democracy. With Rawls' theory, important issues concerning risk distribution are emphasized, and a parallel between social primary goods and risk management is drawn. The hypothetical reasoning should mainly serve as a guide concerning risk issues that affect people who cannot be included in the decision procedure, such as future generations. However, when the affected can be included, an interactive dialogical reasoning is to be preferred. Here, Young's theory is fruitful. It aims at fair decisions by fulfilling conditions of inclusiveness, equality, reasonableness and publicity.